Phylogenetic Reconstruction of Shorebird Lineages Using Mitochondrial Genes (Zoological Archives: An International Journal, 2026)
Shorebirds (order Charadriiformes) constitute one of the most ecologically and morphologically diverse avian radiations,encompassing approximately 360 species distributed across three suborders -- Scolopaci (sandpipers and allies),Charadrii (plovers, stilts, and allies), and Lari (gulls, terns, and allies) -- whose phylogenetic relationships at multiplelevels remain controversial despite decades of molecular systematic study. Deep nodes within Charadriiformes havebeen poorly resolved by individual mitochondrial genes due to rapid Cretaceous-Palaeogene radiation compressed into anarrow temporal window, while shallow nodes within major families show conflicts among published phylogeniesattributable to incomplete lineage sorting and mitochondrial gene tree discordance. This study presents a comprehensivemitochondrial phylogenomics analysis of 284 shorebird species, combining complete mitochondrial genome sequences(n = 84 newly sequenced; n = 200 from GenBank) with targeted amplification of five mitochondrial loci (cytochrome b,ND2, ND5, COI, 16S rRNA) for 200 additional species, producing the largest mitochondrial sequence dataset forCharadriiformes yet analysed. Maximum likelihood (IQ-TREE2) and Bayesian inference (MrBayes 3.2) analyses of theconcatenated 14,847 bp alignment recovered a strongly supported topology (94.7% of nodes with bootstrap support >95)with Lari sister to Charadrii + Scolopaci, resolving a node contested in 18 of 24 previous studies. Time-calibratedBayesian dating places the Charadriiformes crown at 82.4 +- 8.4 Mya (Campanian), with all three suborders divergingwithin 8 million years at the Cretaceous-Palaeogene boundary -- explaining the historical difficulty in resolving this node.The revised phylogeny redefines family-level classification in three instances, and a comprehensive barcode library of284 validated COI sequences is deposited for future identification applications